Do voluntary environmental programs reduce emissions? EMAS in the German manufacturing sector - Roland Kube; Kathrine von Graevenitz; Andreas Löschel; Philipp Massier (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2019)
Voluntary environmental management programs for firms have become an increasingly popular instrument of environmental policy. However, the literature's conclusion on the effectiveness of such programs is ambiguous, and for the European region there is a lack of evidence based on a large control group. We seek to fill this gap with an evaluation of the Eco-Management and Audit Scheme (EMAS), introduced in 1995 by the European Union as a premium certification of continuous pro-environmental efforts above regulatory minimum standards. It is more demanding than other voluntary programs due to annual public reports of the environmental performance and targets for improvements. We use official firm-level production census data on the German manufacturing sector, a major energy consumer and emitter in Europe. To account for the self-selection of firms, we combine the Coarsened Exact Matching approach with a Difference-in-Differences estimation. Our results do not suggest reductions of firms' CO2 intensity and energy intensity neither before nor after certification. Moreover, program participants do not increase renewable energy consumption or investments into the protection of the environment and climate. Our results are robust to a variety of checks and call into question the effectiveness of the EMAS program concerning these particular outcome variables.
Keywords: Q58; Q54; Q48; 330; Voluntary Environmental Programs; Firm-level Energy Behavior; Matching Difference-in-Differences